2014
DOI: 10.1049/iet-rpg.2013.0264
|View full text |Cite
|
Sign up to set email alerts
|

Analytical evaluation of control strategies for participation of doubly fed induction generator‐based wind farms in power system short‐term frequency regulation

Abstract: Increase in doubly fed induction generator (DFIG)-based wind farms degrades the short-term frequency regulation of power systems. However, such wind farms may have large amount of kinetic energy which can be rapidly injected into the power system to support system frequency by using an appropriate supplementary control loop. This study first analyses the impacts of DFIGs and their supplementary loop on power system short-term frequency regulation. Then, the average power system frequency model is modified to i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(31 citation statements)
references
References 28 publications
0
31
0
Order By: Relevance
“…With increasing penetration of wind energy in the grid and stand-alone system, DFIG controllers should be optimally tuned so as to optimize the performance of DFIG wind turbine system during frequency excursion. Reference [21] analyses the impacts of DFIGs and their supplementary loop on power system short-term frequency regulation. The research in the field of inertia International Journal of Electrical Energy, Vol.…”
Section: Droop Controlmentioning
confidence: 99%
“…With increasing penetration of wind energy in the grid and stand-alone system, DFIG controllers should be optimally tuned so as to optimize the performance of DFIG wind turbine system during frequency excursion. Reference [21] analyses the impacts of DFIGs and their supplementary loop on power system short-term frequency regulation. The research in the field of inertia International Journal of Electrical Energy, Vol.…”
Section: Droop Controlmentioning
confidence: 99%
“…The other is virtual inertia control (VIC) [12]; since the WTG itself has mechanical inertia, it has available rotor kinetic energy in operation. The rotor kinetic energy can transform into electromagnetic power through the control algorithm, to provide support for the system frequency, and this process takes a short time and "zero power consumption" [13,14]. In addition, the permeability of wind power is often larger due to the limited capacity of SSM, which ensures the effectiveness of WTG participating in the system transient frequency regulation [15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…The paper [13] introduces a method of PD-VIC to improve the primary frequency contribution of grid-connected variable speed WTG; by adjusting the droop of the WTG in response to wind velocities, the system primary frequency response is significantly improved. In [14], it is concluded that WTG can provide an extra active power production from its stored kinetic energy; the amount of extra injected power is determined according to the frequency deviation Δ and/or the rate of change of frequency / .…”
Section: Introductionmentioning
confidence: 99%
“…However, it does not respond to the frequency change and cannot track the wind, thus can only be used for temporary overproduction [13]. For the VIC, Akbari et al [14] open the feedback control loop and simplify the inertial loop to the integral to exactly predict the frequency nadir; however, the system response and the rotor speed change of the VSWTGs are ignored.…”
Section: Introductionmentioning
confidence: 99%